Islam at a glance - Maulana Sadruddin Islahi (Markazi Maktaba Islami Publishers, 2006)
In this book Islam at a Glance , the redears will find both precision and details. He has employed these devices according to the requirement of each subject. He thought it apt to avoid lenghty debate on those religious topics which are either very well known or are usually stressed upon by those who write and speak about islam and preach it. Those religion matters and aspects which do not fall into this category on which the writers and orators also pay scant attention required comprehensive treatment. Similarly all such religion aspects of which people have not scant knowledge but are even misinformed about, and the full importance of which is not adequately recognised, undeniably deserved to be discussed and argued in detail.